Disseminated tuberculosis associated with deficient interleukin-23/tyrosine kinase 2 signalling. Issue 8 (23rd August 2022) - Ojuawo, Olutobi; Allen, Ryan; Hagan, Guy; Piracha, Shahbaz
Abstract : Tuberculosis (TB) remains a significant cause of morbidity and mortality globally. The disseminated form of the disease has a worse prognosis and is commonly associated with primary and acquired immunodeficiency states such as HIV/AIDS, post-organ transplant and malnutrition. However, disseminated TB in the context of isolated impaired cellular responses to interleukin (IL)-23 due to tyrosine kinase 2 (TYK2) deficiency has been rarely reported. We highlight the case of a young woman with pulmonary and central nervous system TB associated with previously undiagnosed IL-23/TYK2 signalling defects causing impaired response to IL-23. A significant clinical improvement was observed after introduction of adjunctive interferon-gamma therapy to her anti-tuberculous medications. This case emphasises the need to broadly evaluate for potential immune deficiencies in poorly responding patients with fully sensitive TB as well as the potential benefits of interferon-gamma therapy in patients with certain immune defects.